Сleaning of gas emissions of boiler installations of solids - A. V. Dmitriev; V. E. Zinurov; O. S. Dmitrieva; Vu L. Nguyen (Известия высших учебных заведений: Проблемы энергетики)
High performance cleaning of a gas stream of solids of small diameter at small pressure losses in the device is one of key indicators at the choice of the abstersive device. In article, the rectangular separator developed by authors for efficient cleaning of gas emissions of boiler installations of solids is offered. The comparative analysis of a separator with the cyclone СN-11-400 is made. The dependence of hydraulic resistance coefficient from dimensionless geometric factor, it determined the global minimum and the ratio of beam separation elements, which are achieved with minimal energy costs. Results on the efficiency of the proposed separation device are obtained for different values of the length of I-beam elements. In particular, it is shown that with a decrease in the length of I-beam elements, the efficiency of separation of small-diameter particles increases. As a result of the numerical experiment, it was determined that when the length of I-beam elements is equal to 13 mm, the highest efficiency is achieved. At a volume flow rate of Q = 0.444 m3/s, the efficiency of the separator is on average 52% higher than that of the cyclone CN-11-400 when separating gas from particles up to 8 microns in diameter.